Effect of green water concenteration on survival and growth rate of early larvae stage of marble goby, Oxyeleotris marmoratus - Normala Wahap (2008)
This study was conducted to determine the suitability of using tilapia green water for marble goby larval rearing. The other objective by conducting this study is to determnnine the suitable tilapia green water concentration for marble goby larval rearing. The green water used for this study was the green water produced by medium size tilapia with average total length of 17 cm and is cultured in ten ppt. The green water concentration used in this study is 1.5 million cells/ml. 3.0 million cells/ml and 4.5 million cells/ml. The maintenance of green water concentration was carried out everyday to make sure that the concentrations are all the same throughout the experiment. The green water concentration was counted under microscope using haemacytometer. Daily observations were carried out to observe the larvae development and also the behaviour. The survival and growth rate of the larvae were determined and the phytoplankton exist in the tilapia green water was identified. The results shows that larvae reared in 1.5 million cells/ml tilapia green water gives the highest survival with 45.83% survival and also the highest growth with the final total length is 0.532 mm. The larvae reared in this green water survive well indicating that marble goby larvae can be reared in tilapia green water.